2017
DOI: 10.4269/ajtmh.15-0910
|View full text |Cite
|
Sign up to set email alerts
|

Combining Footwear with Public Health Iconography to Prevent Soil-Transmitted Helminth Infections

Abstract: Shoes are effective for blocking soil-transmitted helminths (STHs) that penetrate the skin. Unfortunately, shoe-wearing is uncommon in many areas where STHs are prevalent, in part because local populations are unaware of the health benefits of wearing shoes. This is especially true in low-literacy populations, where information dissemination through written messages is not possible. We launched a public health intervention that combines a public health image with sandals. The image is a "lenticular image" that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The overall incidence and unhygienic behaviors revealed suggest the importance of identifying the best solution to address the STH problem in North Sumatra 26 . In parallel with the increased educational activities, footwear deployment has successfully minimized STH infection in endemic locations 27 . Children of respondents who wear shoes/slippers outside the house had a significantly reduced prevalence of STH infections (72.8%; 95% CI= 62.6, 80.5 vs. 87.0%; 95% CI= 81.4, 91.1).)…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence and unhygienic behaviors revealed suggest the importance of identifying the best solution to address the STH problem in North Sumatra 26 . In parallel with the increased educational activities, footwear deployment has successfully minimized STH infection in endemic locations 27 . Children of respondents who wear shoes/slippers outside the house had a significantly reduced prevalence of STH infections (72.8%; 95% CI= 62.6, 80.5 vs. 87.0%; 95% CI= 81.4, 91.1).)…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological, clinical, environmental, and behavioural factors have been linked to a higher risk of infections by GHPI. These include walking barefoot [ 56 , 65 , 66 ], having a low socio-economic status [ 67 , 68 ], living in rural areas [ 68 , 69 ], having contact with livestock [ 69 71 ], drinking untreated water [ 69 , 72 ], eating unwashed/raw fruit [ 73 ], belonging to a given age group [ 25 , 74 ], having diarrhoea [ 73 ], having a poor nutritional status [ 74 , 75 ], and having anaemia [ 8 , 73 ], among others. A number of studies have demonstrated that wearing shoes considerably reduce the risk of infection by STHs [ 56 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the need for studies to explore whether local populations are unaware of the health benefits of wearing shoes or whether there are socio-economic barriers, e.g. poverty, that lead children to wear shoes occasionally or not at all in this Fijian setting [32].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 98%